The People's Festival enlivens UMPSA's Kembara Prihatin for the Indigenous Community - Nur Hartini, Mohd Hatta (UMPSA, 2024)
CAMERON HIGHLANDS, 27 July 2024 – More than 500 people attended the People's Festival and Gotong-Royong Programme as part of the Kembara Prihatin@Pos Telanok initiative.